2020
DOI: 10.3390/cancers12040968
|View full text |Cite
|
Sign up to set email alerts
|

Acute Promyelocytic Leukemia during Pregnancy: A Systematic Review of the Literature

Abstract: The management of pregnant women with acute promyelocytic leukemia (APL) is a challenging situation where limited evidence-based information is available. We performed a systematic literature review to analyze the outcomes reported for both mother and fetus when APL is diagnosed during pregnancy. PubMed, Scopus and Web of Science databases were systematically searched to identify studies reporting cases of APL during pregnancy. Sixty-six articles met the eligibility criteria (53 single case reports). Ninety-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Pregnancy associated with APL is extremely rare and makes its management more difficult (4)(5)(6). APL and its treatment during pregnancy may lead to maternal complications, such as coagulopathy and abortions, as well as fetal complications, such as preterm birth and intrauterine growth restriction (3). The current study reported the case of a young patient delivering two healthy infants while undergoing treatment for APL.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Pregnancy associated with APL is extremely rare and makes its management more difficult (4)(5)(6). APL and its treatment during pregnancy may lead to maternal complications, such as coagulopathy and abortions, as well as fetal complications, such as preterm birth and intrauterine growth restriction (3). The current study reported the case of a young patient delivering two healthy infants while undergoing treatment for APL.…”
Section: Introductionmentioning
confidence: 81%
“…Although contemporary combined ATRA and ATO therapy is effective in inducing complete remission (CR) in the majority of patients, the use of this regimen remains controversial in pregnant women. ATO has a significant transplacental transport and is highly embryotoxic (2,3). Therefore, its use in pregnancy is not recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Treating pregnant women with acute promyelocytic leukemia (APL) is an extremely difficult situation, where there is limited evidence. The studies found in the literature are limited, and usually concern only a few series of patients [ 66 ].…”
Section: Pregnancy and Oncological Medicinesmentioning
confidence: 99%
“…If the result of the second test is negative, it is recommended to monitor the presence of MRD every 3 months for 2 years. The test should be carried out in the same laboratory to ensure the same level of sensitivity [85]. MRD monitoring with NGS enables the examination of not only specific transcripts, but also potentially other RARA fusion transcripts [76].…”
Section: Measurable Residual Disease Assessmentmentioning
confidence: 99%